Sosialisasi Buku Ajar Maritime English for Navigational Watch Officers di SMK Negeri 10 Padang - Achmad Ali Mashartanto; Slamet Riyadi; Syafni Yelvi Siska; Melda Yanti (Jurnal Surya Masyarakat, 2026)
This community service was held in response to the initial finding that Maritime English instruction at SMK Negeri 10 Padang remains hampered by a lack of textbooks aligned with IMO Model Course 3.17, limited teacher training, and students’ insufficient mastery of navigational terminology. The project introduced and disseminated the textbook Maritime English for Navigational Watch Officers developed according to IMO, SMCP, technical terminology, formative exercises, a glossary, and supporting visual resources. A participatory outreach methodology was employed, comprising presentations, group discussions, maritime communication simulations, and a practicality questionnaire. This event took place on 21 July 2025 in the school prayer hall, with participants including Poltekpel Sumbar team, SMK Negeri 10 Padang’s teachers, teaching staff, and students. Quantitative results indicated average “Yes” practicality scores of 70 % from 17 teachers and 83 % from 40 students, particularly regarding ease of use, engaging design, and support for independent learning; concerns remained over textbook ownership and the potential to replace teacher presence. Qualitative feedback underscored the need for online modules, a translated edition, audio–video content, and field visits to Poltekpel Sumbar. The discussion highlights the effectiveness of bilingual instruction, scaffolding, dialogic teaching, and experiential learning in enhancing navigational watch officer competencies. Pedagogical implications include enriching contextual and interactive media; institutional implications stress the importance of formal MoUs, sustainable funding, and local cadre teams; strategic implications advocate for additional ESP maritime titles and digital platforms. The project is envisioned as a replicable model for vocational collaboration to bolster graduate competitiveness in the global shipping industry.